2014
DOI: 10.5539/ijef.v6n10p259
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Operational Efficiency on the Future Performance of Indian Manufacturing Firms

Abstract: This study investigated the relationship between changes in operational efficiency and changes in future performance of Indian manufacturing firms applying a correlational research design. A sample of 244 firms was selected from the top 500 companies listed on the Bombay Stock Exchange (BSE) for a period of five years (from 2008-2012). The findings of this study indicate that changes in operational efficiency play a role in the future performance of Indian manufacturing firms. This study contributes to the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…This economic value often takes the form of working capital savings. Producing more output from unchanged input, consuming less input for unchanged output, reducing operating costs without damaging the corporation, reducing the days in the cash conversion cycle, improving operating cash flows, increasing total asset turnover, and effecting reductions in operating risk are all signs of relative operational efficiency (Gill et al, 2014;Owolabi and Obida, 2012).…”
Section: Tobin's Q Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…This economic value often takes the form of working capital savings. Producing more output from unchanged input, consuming less input for unchanged output, reducing operating costs without damaging the corporation, reducing the days in the cash conversion cycle, improving operating cash flows, increasing total asset turnover, and effecting reductions in operating risk are all signs of relative operational efficiency (Gill et al, 2014;Owolabi and Obida, 2012).…”
Section: Tobin's Q Indexmentioning
confidence: 99%
“…Operating expense has been used to measure efficiency in some studies either alone or in relation to revenue or total assets (Ghebregiorgis and Atewebrhan, 2016;Al-Jafari and Alchami, 2014;Gill et al, 2014) The rising costs of imports and private generation of electricity and other vital infrastructures to sustain production processes result in high cost of production, increase in product prices, and consequently reduction in consumer demand (Adegbie and Adeniji, 2013). The high fuel import bill (16% of total imports) highlights the need for investment in oil refineries (African Business Magazine, 2017).…”
Section: Operating Expensesmentioning
confidence: 99%
“…Some empirical studies have similar findings indicating that operational efficiency commitment to environmental friendliness can affect firm performance. These studies include Al-Tuwaijri et al (2004), Moneva and Ortas (2010), Purnomo et al (2012), Gill et al (2014) and Muhammad et al (2015). An empirical study by Al-Tuwaijri et al (2004) examined the relationship between environmental performance and economic performance.…”
Section: The Effect Of Operational Efficiency Commitment To Environmementioning
confidence: 99%
“…The results of their study indicated that firms with a good environmental management system are those with the better environmental performance, which in turn delivers a positive impact on financial performance. Gill et al (2014) affirmed that firms with capacity to increase operational efficiency may generate a positive effect on their future performance. Muhammad et al (2015) discovered that environmental performance positively impacts financial performance and firm value.…”
Section: The Effect Of Operational Efficiency Commitment To Environmementioning
confidence: 99%
See 1 more Smart Citation